Adverse Treatment Outcomes among Tuberculosis Patients Enrolled Under Directly Observed Treatment Strategy in Murang'a County: A crossectional study. - Shiguri, Fredrick Mmbono; Gachohi, John; Mokaya, Daniel (International Journal of Health Sciences, 2024)
Purpose: Despite advances in TB control, over 20% of TB patients in low and middle income countries end up with adverse treatment outcomes. We aimed to describe adverse treatment outcomes and explore the associated factors among TB patients enrolled in Murang'a county between 2017 and 2019. Methodology: We conducted a crossectional study in which data was abstracted from patients records and analysed using Computer package (SPSS 24). Univariate and Multivariate analyses were done to describe relationships between individual or confounding independent variables and treatment outcomes. (p<0.05) and 95% CI. Incidence rate ratio and Odds ratio (OR) were calculated to asses effects of variables and strength of relationships. Findings: Of 4414 participants, 87.4 % were aged â‰¤54 years, 57.8% were underweight and 21.5% were HIV positive. 7.5 % had adverse treatment outcomes with 85.3% dying, 9.6% failing and 5.1% converting to multi-drug resistance. Older age, underweight, being treated in Health centers and Hospitals, and negative mycobaterial test result were attributed to death, while older age, Male gender and negative or unknown mycobacterial test results predicted an adverse treatment outcome. Our study demonstrated importance of separate analyses for single and aggregated outcome, MDRTB as a treatment outcome and revealed un-known and negative myco-bacteriological test results as factors for death. Unique contributor to theory, policy and practice: Special attention such as direct government funds transfer, treatment support, and close clinical care is reccommended for elderly patients to cater for inequities in their access to health care, and general welfare so as to prevent death and other adverse treatment outcomes among them. Behavior change programs should be prioritized for male patients to address substance abuse, poor health seeking behaviour and treatment adherence. Strict management, close monitoring and nutrition support is reccommended for patients treated in hosptals and health centers, and those at risk or already immune compromised such as the elderly, undernourished and those with co-morbidities . Strict case management and adherence counseling for patients with un-known sputum status as well as a further enquiry into the association between un-known sputum status and deaths is reccommended